The Impact of Ownership Structure and Board Characteristics on Tax Avoidance - Andy Lim; Meiliana Suparman (Universitas Muhammadiyah Makassar, 2022)
This study examines the impact of ownership structure and board characteristics on tax avoidance. A tax avoidance measure is the effective tax rate (ETR) and cash flow effective tax rate (CFETR). While the ETR quantifies taxable income, the CFETR demonstrates the difference between total tax expense and operating cash flows. The ownership structure includes managerial, institutional, foreign, family, and concentrated ownership. The size, independence, frequency of meetings, and gender diversity of the board indicate board characteristics. A purposive sampling method was used to select non-financial companies listed on the Indonesia Stock Exchange between 2017 and 2021. Results indicate a significant positive effect of concentrated ownership and independent directors is found on tax avoidance (ETR and CFETR). On the other hand, the size of the board directors negatively impacts tax avoidance (ETR and CFETR). Furthermore, tax avoidance (ETR and CFETR) is unaffected by managerial, institutional, foreign, and family ownership, meeting frequency, and board gender diversity. The results of this study are still contradictory and not in line with previous studies because it includes data from the pandemic period. It implies the need for improvements in the implementation of good governance in order to achieve more profits through tax avoidance. A comprehensive governance system must ensure that every element plays a significant and active role in reducing the tax burden of a company within the legal corridor (tax avoidance)